2010
DOI: 10.2337/db09-1918
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Deficiency Causes Insulin Resistance Induced by Uncontrolled Diabetes

Abstract: OBJECTIVEDepletion of body fat stores during uncontrolled, insulin-deficient diabetes (uDM) results in markedly reduced plasma leptin levels. This study investigated the role of leptin deficiency in the genesis of severe insulin resistance and related metabolic and neuroendocrine derangements induced by uDM.RESEARCH DESIGN AND METHODSAdult male Wistar rats remained nondiabetic or were injected with the β-cell toxin, streptozotocin (STZ) to induce uDM and subsequently underwent subcutaneous implantation of an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
140
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(162 citation statements)
references
References 51 publications
15
140
0
4
Order By: Relevance
“…While leptin therapy suppresses glucagon levels in STZdiabetic mice [2-5, 7, 19], leptin therapy can reverse hyperglycaemia prior to glucagon suppression [11], and can reverse hyperglucagonaemia without normalising glycaemia in STZ-diabetic rats [5]; this suggests that glucagon suppression alone cannot sufficiently account for the glucoselowering action of leptin. Our finding that, during prolonged fasting, STZ-leptin mice showed a trend towards elevated plasma glucagon, but were hypoglycaemic, supports this notion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While leptin therapy suppresses glucagon levels in STZdiabetic mice [2-5, 7, 19], leptin therapy can reverse hyperglycaemia prior to glucagon suppression [11], and can reverse hyperglucagonaemia without normalising glycaemia in STZ-diabetic rats [5]; this suggests that glucagon suppression alone cannot sufficiently account for the glucoselowering action of leptin. Our finding that, during prolonged fasting, STZ-leptin mice showed a trend towards elevated plasma glucagon, but were hypoglycaemic, supports this notion.…”
Section: Discussionmentioning
confidence: 99%
“…First, this demonstrates that the level of glycaemic normalisation achieved by leptin is dependent on fasting duration, which should be taken into account when comparing results across studies. Differences in fasting duration could account for discrepancies between studies as to whether physiological leptin doses reverse hyperglycaemia in STZ-diabetic rodents [5,11,20], and why studies examining free-feeding or 2 h fasted rodents have not reported leptin-induced hypoglycaemia [2,3,7,19]. Second, the hypoketotic hypoglycaemia observed during prolonged fasting suggests that leptin therapy may carry hypoglycaemic risk in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that obesity can be a result of leptin resistance, leptin resistance is likely to be involved in the development of the disease. Like Leptin resistance, leptin deficiency is significant in the pathogenesis of severe insulin resistance in uncontrolled insulin deficient diabetes mellitus [26].…”
Section: Leptin and Diabetesmentioning
confidence: 99%
“…[25] 2004 Leptin level increases with sleep [7] 2010 Leptin is significant in the pathogenesis of insulin resistance in uncontrolled insulindeficient diabetic rats [26] 2016…”
mentioning
confidence: 99%